Polymorphism of chemokine receptor gene CCR5 in multiple sclerosis patients and in healthy subjects in the Siberian region - Yu. Yu. Orlova; V. M. Alifirova; N. V. Cherdyntseva; P. A. Gervas (Бюллетень сибирской медицины)
Multiple sclerosis is chronic inflammatory disease of the central nervous system in the development of which chemokines of the type Tx1 play the leading role. Chemokines and their receptors participate in the development of multiple sclerosis as a result of drawing immune cells into central nervous system. Mutation of CCR5 delta32 decreases functional activity of the appropriate receptor on cellular surface and thus can reduce migration of leucocytes into foci of injury. Aimed at studying the role of mutation in multiple sclerosis, we compared frequency of gene type CCR5 in peripheral mononuclears of 102 multiple sclerosis patients and in 136 healthy subjects. The results obtained allow to conclude that polymorphism of chemokine receptor gene CCR5del32 is not a leading factor in the susceptibility to multiple sclerosis in the studied population.